2020
DOI: 10.3390/microorganisms8010099
|View full text |Cite
|
Sign up to set email alerts
|

Thymol Inhibits Biofilm Formation, Eliminates Pre-Existing Biofilms, and Enhances Clearance of Methicillin-Resistant Staphylococcus aureus (MRSA) in a Mouse Peritoneal Implant Infection Model

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a common human pathogen that causes several difficult-to-treat infections, including biofilm-associated infections. The biofilm-forming ability of S. aureus plays a pivotal role in its resistance to most currently available antibiotics, including vancomycin, which is the first-choice drug for treating MRSA infections. In this study, the ability of thymol (a monoterpenoid phenol isolated from plants) to inhibit biofilm formation and to eliminate mature biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 67 publications
2
30
0
2
Order By: Relevance
“…These studies corroborate our results that not only 7 mg of PCL-THY eliminate already formed biofilms but also that the exposition to 5 mg PCL-THY for 24 h reduces bacterial attachment to the well. The obtained results may evidence that cell wall damage can negatively affect bacterial attachment as we previously described, which, according to Kerekes et al represents the first step in biofilm formation, followed by formation of microcolonies, maturation, and cell dispersal. ,, The effect of THY against bacterial adhesion has also been demonstrated by Yuan et al when they analyzed PIA (polysaccharide intracellular adhesion), a component involved in adhesion and aggregation. This component was reduced under the presence of THY, and thus, bacteria could adhere to materials at the initial stage, but they were unable to form biofilms due to a reduced cell-to-cell adhesion. , Therefore, THY reduces bacterial growth, interferes with biofilm formation, and promotes biofilm eradication …”
Section: Results and Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…These studies corroborate our results that not only 7 mg of PCL-THY eliminate already formed biofilms but also that the exposition to 5 mg PCL-THY for 24 h reduces bacterial attachment to the well. The obtained results may evidence that cell wall damage can negatively affect bacterial attachment as we previously described, which, according to Kerekes et al represents the first step in biofilm formation, followed by formation of microcolonies, maturation, and cell dispersal. ,, The effect of THY against bacterial adhesion has also been demonstrated by Yuan et al when they analyzed PIA (polysaccharide intracellular adhesion), a component involved in adhesion and aggregation. This component was reduced under the presence of THY, and thus, bacteria could adhere to materials at the initial stage, but they were unable to form biofilms due to a reduced cell-to-cell adhesion. , Therefore, THY reduces bacterial growth, interferes with biofilm formation, and promotes biofilm eradication …”
Section: Results and Discussionsupporting
confidence: 73%
“…In this sense, Yuan et al also showed the efficiency of free THY in the inhibition of biofilm obtained from the non-clinical MRSA strain TCH1516 (ATCC BAA-1717). Biofilm formation and mature biofilm were inhibited by the treatment with up to 512 μg/mL of free THY, a concentration much higher than those released from our mats, though not achieving the complete eradication of bacteria growth . Moreover, Cabarkapa et al treated bacteria (Salmonella enteritidis) with sub-MIC (MIC/2-MIC/4) concentrations of Origanum and Thymus EOs as well as their active components carvacrol and THY, and results showed that biofilm formation was inhibited .…”
Section: Results and Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In our study, biofilms were left to be formed for 48 h under static conditions, resulting in both species achieving biofilm populations of over 10 7 CFU/cm 2 by the end of incubation (just before disinfection; results not shown). Such cell-concentration levels are considered adequate for sufficient (mature) biofilm formation (and not just individual cells attachment), with many other previous studies having left staphylococci to form biofilms on PS microtiter plates for just 24 h before further experimentation [59][60][61]. However, we still do not have any other further info regarding the structure and composition of the extracellular material of the biofilms formed here or whether and in which way these characteristics, together with the variation in biofilm incubation time (or many other parameters that could potentially influence biofilm growth), could affect the resistance of the enclosed bacteria to the tested antimicrobials.…”
Section: Discussionmentioning
confidence: 99%